The Effectiveness of Multiple Intelligences (MI)-Based English Classroom Activities at The Eleventh Grade Students of SMAN 2 Mamuju of West Sulawesi - Ridwan, Asriani (ELT WORLDWIDE, 2015)
The objectives of this research were to find out: (1) the studentsâ MI profiles, (2) whether the implementation of MI-Based English Classroom Activities could increase the studentsâ English achievement or not, and (3) whether the students are interested toward the implementation of MI-Based English Classroom Activities or not. This research was conducted through Quasi-Experimental Method. The population of the research was the eleventh grade students of the second semester in SMAN 2 Mamuju of West Sulawesi Province in 2014/2015. This sample was selected through purposive random sampling technique. The data of the research were analyzed inferential and descriptive statistic. The results of the research were: (1) the studentsâ MI profiles showed 80.6 % students in existential and interpersonal intelligences, 74.2 % students in verbal-linguistic and naturalist intelligences, 67.7 % students in logical-mathematical and musical intelligences, 58.1 % students in visual-spatial intelligence, 51.6 % students in bodily-kinesthetic and intrapersonal intelligences, (2) the implementation of MI-Based English Classroom Activities could increase studentsâ English achievement (3) The students were interested toward the implementation of MI-Based English Classroom Activities. So it can be concluded that the implementation of MI-Based English Classroom Activities was very effective to be applied in increasing the studentsâ English Achievement. Key words: Multiple Intelligence (MI) and English Classroom Activities.